QCA BASED SECURE NANOCOMMUNICATION BLOCK CIPHER DESIGN BASED ON ELECTRONIC CODE BOOK - Chandra Das, Jadav; De, Debashis (Malaysian Journal of Computer Science, 2018)
In nanotechnology, Quantum Dot-Cellular Automata (QCA) is a new paradigm that can serve as an alternative to CMOS circuits. In comparison to CMOS, QCA has lower device area and faster processing power with an overall low energy consumption. The complexity of cryptographic architecture is a key issue in terms of circuit density and power dissipation.Moreover, security is the major issue in nanocommunication systems. Those issues can be overcome through QCA technology. To date, only few applications of QCA have been explored in the field of cryptography. This paper illustrates the QCA design and implementation of block cipher based on electronic code book (ECB). An encoder circuit, which can function as decoder for ECB is proposed. The design requires only 0.095 Î¼m2 area and a latency value of 0.75. The circuit dissipates very low energy which is established through calculation of power dissipation. Due to inherent characteristics, side channel attacks like power analysis attack can be prohibited using proposed circuit. The circuit is implemented on QCA Designer platform and the design accuracy is verified via simulation results.